William shakespeare's star wars ebook Verily, a new hope. - Doescher, Ian (William Shakespeare's Star Wars, 2013)
The New York Times Best Seller Experience the Star Wars saga reimagined as an Elizabethan drama penned by William Shakespeare himself, complete with authentic meter and verse, and theatrical monologues and dialogue by everyone from Darth Vader to R2D2. Return once more to a galaxy far, far away with this sublime retelling of George Lucas’s epic Star Wars in the style of the immortal Bard of Avon. The saga of a wise (Jedi) knight and an evil (Sith) lord, of a beautiful princess held captive and a young hero coming of age, Star Wars abounds with all the valor and villainy of Shakespeare’s greatest plays. Authentic meter, stage directions, reimagined movie scenes and dialogue, and hidden Easter eggs throughout will entertain and impress fans of Star Wars and Shakespeare alike. Every scene and character from the film appears in the play, along with twenty woodcut-style illustrations that depict an Elizabethan version of the Star Wars galaxy. Zounds! This is the book you’re looking for.